Pensamientos automáticos y su influencia en el trastorno adaptativo con ansiedad en una joven de 18 años del cantón Pelileo Provincia del Tungurahua - Villacis Ramos, Olga Patricia (2021)
Within this case study, the problem presented will be directly addressed, which is how automatic thoughts influence the adjustment disorder with anxiety in an 18-year-old woman from the Pelileo canton of Tungurahua province. This problem occurs due to a change of residence from the city of Quito to Pelileo, the young woman has presented significant changes in her general, school and social behavior, as well as in the cognitive, which have directly affected her adaptation, causing her symptoms. both cognitive and somatic. Within this case study, a qualitative methodology is used for the interpretation and description of the problem, accompanied by instruments and techniques for psychological application and diagnosis, such as the psychological interview, the medical history and the psychometric tests such as the automatic thoughts questionnaire. and the Hamilton anxiety test. The patient was determined a Psychodiagnosis of adjustment disorder with anxiety where it was necessary to evaluate the areas where problems have existed due to this alteration in adaptability presenting both problems and in their interpersonal relationships in family relationships and academically and also likewise in terms of their cognitions.